Reducing clinical review burden for insertable cardiac monitors. (24th May 2021) - Gardner, RS; Quartieri, F; Betts, TR; Afzal, M; Manyam, H; Badie, N; Dawoud, F; Sabet, L; Davis, K; Qu, F; Ryu, K; Ip, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The insertable cardiac monitor (ICM) is an essential tool for the ambulatory diagnosis of arrhythmias. However, definitive diagnoses still rely on time-consuming, manual adjudication of electrograms (EGMs) transmitted to the patient care network. This EGM review burden may be minimized by automatically selecting a subset of EGMs for fast review without delaying the diagnosis. Purpose: Develop EGM selection strategies to reduce the EGM review burden without delaying diagnoses. Methods: A retrospective analysis of 1, 000 randomly selected Abbott Confirm Rx devices with 90+ days of remote transmission history was performed, regardless of transmission frequency, and all EGMs were adjudicated as either true or false positive (TP, FP). Up to 3 EGMs per day per arrhythmia type were prioritized for review based on ventricular rate and episode duration, with rules specific to each arrhythmia type: atrial fibrillation (AF), tachycardia, bradycardia, and pause. The resulting reduction in EGM review burden and TP days (patient-days with at least 1 TP EGM), as well as any diagnostic delay from the first transmitted TP, were calculated relative to reviewing all transmitted EGMs. Results: In this population and transmission period, at least one AF, tachycardia, bradycardia, and pause EGM was transmitted by 424, 343, 190, and 325 unique devices, respectively, with a total of 35, 723, 12, 239, 19, 752, and 28, 002 EGMs, and a total of 6, 163, 1, 572, 1, 438, and 646 TP days. For these patients with ≥1 EGM, the median [IQR] EGM transmission rate was 2.6 [0.7, 11.6], 1.1 [0.4, 4.7], 2.1 [0.6, 10.7], and 3.4 [0.6, 29.9] EGMs/patient/month, respectively. The optimal EGM selection strategy reduced this EGM review burden by 43%, 67%, 76%, and 50%, while only missing 3.4%, 2.2%, 0.3%, and 0.2% of TP days, respectively. Ultimately, 97%, 99%, 99%, and 99% of devices with a TP AF, tachycardia, bradycardia, or pause EGM exhibited no diagnostic delay vs. reviewing all transmitted EGMs. Conclusion: EGM prioritization rules for selecting up to 3 episodes/day significantly reduced EGM burden across all patients, not just "frequent fliers, " with no delay-to-diagnosis in >97% of patients who exhibited a true arrhythmia. Implementing these rules on the patient care network may improve clinical workflow and ICM patient management.